24-h movement behaviour, thermal perception, thirst, and heat management strategies of children and adults during heat alerts: a pilot study - Ravanelli, Nicholas; Morris, Nathan; Morrison, Shawnda A. (Frontiers in Physiology, 2023)
ABSTRACT Background: Heat waves caused by climate change are increasingly challenging the wellbeing of individuals across the lifespan. Current efforts to understand the thermal perceptions and behaviours of people throughout the lifespan during heat waves are limited. Methods: Since June 2021, the Active Heatwave project has been recruiting households to better understand how individuals perceive, cope, and behave during heat waves. Using our novel web platform, participants were prompted to answer our Heat Alert Survey on days when a participants geolocation corresponded to a broadcasted local heat alert. Participants provided 24-hour movement behaviour, thirst, thermal perception, and cooling strategies via validated questionnaires. Results: A total of 285 participants (118 children) from 60 distinct weather station locations globally participated between June and September 2021 and 2022. At least 1 heat alert (834 total) were identified from 95% (57/60) of the weather stations. Children reported spending more time performing vigorous intensity exercise compared to adults (p<0.05), but no differences in thermal sensation, thermal comfort, or thirst sensation (all P>0.31) were observed. For thirst management, 88% of respondents used water to relieve thirst, although notably, 15% of adults reported using alcohol. Regardless of age, staying indoors was the most common heat management strategy, whereas visiting cooling centres was the least. Conclusion: The present study presents a proof-of-concept combining local heat alert notifications with e-questionnaires for collecting near-real-time perceptual and behavioural data for both children and adults during heat waves. The observed patterns of behaviour suggest that present public heat-health guidelines are often ignored, children engage in fewer heat management strategies compared to adults, and these disparities highlight the need to improve public health communication and knowledge dissemination around promoting effective and accessible cooling solutions for children and adults.